Evaluasi keragaman genetic berbagai galur murni jagung manis utnuk penentuan tetua hibrida - Arya Widura Ritonga; Dwiwanti Sulistyowati; Candra Budiman; Ahmad Zamzami; Okti Syah Isyani Permatasari (Jurusan Agroteknologi, 2023)
Sweet corn is one of the most popular crops in Southeast Asian countries, including Indonesia. Superior sweet corn varieties breeding is important to do in order to improve the quality and productivity of sweet corn in Indonesia. Plant breeding programs rely on genetic quality variability and heritability information. Therefore, this study aimed to evaluate the performance and genetic variablity of various sweet corn inbred lines to determine the best prospective parents for hybridization. The study was conducted at the Leuwikoppo experimental field of the Department of Agronomy, Faculty of Agriculture, IPB, from January to March 2022. Twelve sweet corn inbred lines were planted in the field using a completely randomized block design with three replications. Analysis of variance, estimation of the genetic parameters, broad sense heritability, genetic and phenotypic coefficients variability and cluster analysis were carried out in this study. The results showed that there were differences in qualitative and quantitative characters between the tested sweet corn genotypes. Plant height, ear height, stem diameter, ear length, and ear weight had a high broad sense heritability and moderate to high of genetic coefficients of variability. SM12-2 and T10-3 lines become the prospective parents generating a high cob weight and seed sweetness.ABSTRAK Jagung manis merupakan salah satu tanaman yang sangat populer di negara-negara Asia tenggara, termasuk Indonesia. Hal ini menjadikan perakitan varietas unggul jagung manis dengan produktivitas dan kualitas tinggi perlu dilakukan. Informasi keragaman genetik sangat penting dalam program pemuliaan tanaman. Penelitian ini bertujuan untuk mengevaluasi keragaan dan keragaman genetik berbagai galur jagung manis sehingga dapat diperoleh tetua potensial untuk pembentukan hibrida F1 jagung manis. Percobaan dilakukan di Kebun Percobaan Leuwikoppo, Departmen Agronomi, Fakultas Pertanian, IPB, dari bulan Januari sampai Maret 2022. Sebanyak 12 galur murni jagung manis ditanam menggunakan rancangan kelompok lengkap teracak dengan 3 ulangan. Data diolah dengan menggunakan analisis ragam, pendugaan parameter genetik komponen ragam, heritabilitas arti luas, koefisien keragaman genotipik dan fenotipik serta analisis kluster. Hasil penelitian menunjukkan adanya perbedaan pada karakter kualitatif dan kuantitatif diantara galur jagung manis yang diuji. Selain itu, diperoleh informasi bahwa karakter tinggi tanaman, tinggi tongkol, diameter batang, panjang tongkol, dan bobot tongkol memiliki nilai heritabilitas yang tinggi serta nilai koefisien keragaman genetik kategori moderat sampai tinggi. Berdasarkan penelitian ini, galur jagung manis SM12-2 dan T10-3 merupakan tetua yang potensial menghasilkan bobot tongkol dan kemanisan biji yang tinggi.